Aplikasi Metode DRASTIC untuk Analisis Kerentanan Air Tanah terhadap Pencemaran di Kabupaten Tanah Laut, Kabupaten Banjar, dan Kota Banjarbaru, Provinsi Kalimantan Selatan - Thomas Triadi Putranto; Mochamad Arief Budihardjo; Anik Sarminingsih (Diponegoro University, 2022)
In 2017-2019, the Tanah Laut Regency, Banjar Regency, Banjarbaru City population was relatively high and continued to increase every year. The increase in the population reaches 1.39% to 2.92%. Along with population growth, the human need for clean water also increases, especially from groundwater. The study aims to assess the vulnerability of groundwater to contamination. The method used for the analysis of groundwater vulnerability to contamination is the DRASTIC method. It refers to seven parameters, namely groundwater depth (D), net recharge (R), aquifer media (A), soil layer (S), topography (T), impact to vadose zone (I) and hydraulic conductivity (C) by using geospatial analysis to calculate the DRASTIC Index/DI. From the results of geospatial analysis, there are three zones of groundwater vulnerability to contamination based on DI values, namely low vulnerability (95-106), medium vulnerability (106-146), and high vulnerability (146-186). The distribution of high zones dominates in the research area around of 75, 8%. The DRASTIC method requires a lot of data to provide an accurate analysis of groundwater vulnerability zone maps. This method has excellent accuracy and more effective in producing a map of the groundwater vulnerability zones to contamination.